The temporal and kinematic constraints on the early Alpine orogen: insights from Rb–Sr geochronology and geological mapping of the Avers nappe (Eastern Swiss-Alps) - Vidar Jakobsson; Johannes Glodny; Uwe Ring; Alasdair Skelton (Swiss Journal of Geosciences)
Abstract Understanding temporal shifts of thrust transport direction and the interplay between thrusting and normal faulting during mountain building is important for better understanding orogeny. Current tectonic models of the Alps envisage Cretaceous E–W directed thrusting and subsequent extension in the same direction, mainly preserved in the upper plate (Austroalpine unit), followed by Paleogene N–S shortening. The Austroalpine-Pennine boundary region is at the transition between dominantly E–W and N–S directed orogenic movements. This study focuses on metabasite rocks of the Pennine Avers nappe, which retain evidence for early E–W directed shortening extending into the Eocene, thus conflicting with the standard orogenic models. Our new kinematic and geochronological constraints from the Avers nappe demonstrate that top-to-the-W nappe imbrication progressed into the South Pennine realm under blueschist facies conditions. Rb–Sr multimineral isochron ages constrain the waning stages of top-to-the-W shear between 47.26 ± 0.26 and ≥ 43.5 ± 0.6 Ma (2σ uncertainties). Subsequent deformation during incipient decompression from blueschist-facies metamorphism associated with N–S shearing occurred between 41.1 ± 1.7 and 40.7 ± 1.6 Ma. A summary of previously published geochronological and kinematic data shows that Cretaceous to Eocene (until ≥ 43.5 ± 0.6 Ma) deformation is best described by an overcritically tapered orogenic wedge model. The subsequent deep underthrusting and underplating of the distal European margin is considered to have caused a change in orogenic wedge dynamics, leading to extruding wedge tectonics associated with N–S shortening.